The Role of Vitamin D and Hepcidin in Pathophysiology of Anaemia in Children with Chronic Kidney Disease - Hertanti Indah Lestari (Fakultas Kedokteran Universitas Sriwijaya, 2020)
In patients with Chronic Kidney Disease (CKD), renal function in maintaining the homeostasis of various metabolic systems of the body is impaired, one of which is the production of erythropoietin hormones. Anaemia is a frequent complication of the CKD and contributes to the increased morbidity and mortality of the patients. Diagnosis or treatment of anaemia in PGK is still a challenge due to multifactorial. Hepcidin, a peptide that has been known as an acute-phase protein, plays a vital role in the regulation of iron metabolism. Hepcidin is known to correlate with ferritin, a parameter of anaemia screening which is commonly examined during this time. In addition to the role of pathophysiology anaemia in CKD, hepcidin is currently widely researched because it is suspected to contribute also to the pathophysiology of bone mineral disorders in PGK. Current research shows that the concentration of vitamin D is inversely proportional to the concentration of hepcidin and is positively associated with the concentration of haemoglobin and iron. The latest report invitro and in vivo support the existence of the interaction between vitamin D and anaemia in patients with PGK through the role of hepcidin.Keywords: anemia, hepcidins, vitamin D, erythropoietin, chronic renal insufficiency.